Effect of Questioning Technique on Critical Thinking Skills in the Subject of Chemistry at Secondary Level - Irfan, Muhammad (JSE, 2025)
In contemporary science education, fostering students’ critical thinking has become a pedagogical imperative, yet classroom practices often rely on lower-order questioning that limits cognitive growth. The present study investigates the effect of questioning technique on the development of inference and argumentation skills among secondary school students in the subject of Chemistry in Federal Government Educational Institutions (Cantt. & Garrison), Kharian Region, District Gujrat. Guided by Bloom’s Taxonomy and constructivist learning theory, a quasi-experimental design was adopted involving 67 students of science of Grade 9 divided into control and experimental groups. The experimental group received instruction through structured higher-order questioning strategy for six weeks, while the control group experienced traditional teacher-led instruction. Pre- and post-tests measuring two critical thinking dimensions inference and argumentation were administered. Statistical analysis using independent t-test revealed significant improvement in the experimental group’s overall critical thinking performance, particularly in inference, deduction and interpretation domains. These findings affirm that well designed questioning frameworks can transform science teaching from rote learning to active inquiry. The study provides empirical support for integrating questioning-based pedagogies into Chemistry education and highlights the need for professional development programs that train teachers in promoting higher-order thinking across secondary science curricula.